Metronidazole-Induced Encephalopathy in a Patient with Hypothyroidism and Diarrheal Disease: A Case Report - Zainab Iftikhar (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Metronidazole is a common antimicrobial agent that is active against anaerobic bacteria and protozoa. Although usually well tolerated, it has rare but severe side effects like metronidazole-induced encephalopathy (MIE), with its prolonged use. Case presentation: We present the case of a 40-year-old woman with a past history of hypothyroidism and chronic diarrhoea who had a 6-month history of dizziness and a 1-month history of ataxia and numbness. She had been sporadically consuming animal metronidazole for many years. Neurological examination was positive for cerebellar signs, glove-and-stocking hypoesthesia, and brisk reflexes. MRI of the brain revealed T2 hyperintense lesions in the dentate nuclei of the cerebellum. Cervical spine imaging demonstrated mild degenerative changes, and nerve conduction studies showed sensory-motor axonal polyneuropathy. Lab tests were significant for deranged liver function tests. A diagnosis of MIE was established on the basis of clinical presentation, chronic metronidazole use, and ruling out other causes. Treatment was discontinuation of metronidazole, intravenous hydration, and steroids. The patient significantly improved and was discharged with follow-up. At 2-month follow-up, she had no symptoms, and repeated MRI demonstrated radiological improvement. Conclusion: This case illustrates the need to recognize MIE, particularly in patients exposed to metronidazole chronically. Prompt diagnosis and withdrawal of the causative agent are essential for full recovery. Keywords: Hypothyroidism, Metronidazole toxicity, Dentate nuclei, T2 hyperintense lesions